Preventing emergency readmissions to hospital - Nolte, Ellen; Roland, Martin; Guthrie, Susan; Brereton, Laura (RAND Corporation, 2023)
The study reports on the evidence and potential for use of ‘emergency readmissions within 28 days of discharge from hospital’ as an indicator within the NHS Outcomes Framework, drawing on a rapid review of systematic reviews.